Spectrum of Biopsy Proven Glomerular Disease: An Experience Based on Light Microscopy and Direct Immuno tluorescence Microscopy - Habib, MA; Badruddoza, SM; Meherunnesa, -; Uddin, M Jalal; Ahmed, F; Chowdhury, NI; Hossain, MT; Mahmood, I (TAJ: Journal of Teachers Association, 2009)
Glomerular diseases continue to be the leading cause of end-stage renal disease globally. In this study, 80 adequate renal biopsy specimens were subjected to histopathology and direct immunofluorescence (DIF) microscopy in the Department of Pathology, Rajshahi Medical College, from July 2008 to June 2009, to evaluate the spectrum of glomerular disease. Of them 42.5% were male and 57.5% were female with ratio 1: 1.35. The most frequent clinical presentation was nephrotic syndrome (62.5%). Primary glomerular diseases was accounting for 91.25 % of all glomerular disease and of them; FSPGN was the most common histological lesion (27.4%). DMesPGN was the second most common lesion 17.8%) followed by MCD (15.07%), MGN (10.96%), FSGS (10.96%), lgA nephropathy (6.85%), CSG (2.74%) and Cres. GN (2.74%). Lupus nephritis was the most prevalent (71.43%) among secondary glomerulonephritis cases. Among 73 adequate cases for DIF, 63.01% were found to be DIF positive and lgG alone and in various combinations were found in 82.60 % cases (highest deposits). TAJ 2009; 22(1): 239-244